Differentiating hypoglycemia awareness status from hypoglycemia experience in tools for measuring impaired awareness of hypoglycemia - Eduardo Sepúlveda (2020)
Background:Developing technologies in real-time continuous glucose monitoring (CGM) are successfully reducing severe hypoglycemia (SH) in trials and clinical practice. Their impact on impaired awareness of hypoglycemia, a major risk factor for SH, is uncertain. Methods:The present study examined two scales for assessing hypoglycemia awareness status, the Gold score and the eight-item Minimally Modified Clarke Hypoglycemia Survey (MMCHS), commonly used in trials of CGM, in Portuguese-speaking adults with type 1 diabetes and conducted an exploratory factor analysis on MMCHS. Results:A bifactorial structure in MMCHS was revealed, with a clear distinction between items that measure SH experience and those that measure hypoglycemia awareness status. The latter is associated with the same risk for SH as the Gold score. Conclusions:We conclude that improvement in awareness scores by the MMCHS may reflect only a reduction in SH with no restoration of endogenous awareness, making the current literature consistent in evidence that CGM does not improve endogenous awareness and nonsensor supported protection from SH. This has implications for risk of SH when CGM is not being worn.